Protein kinase B (AKT) regulates SYK activity and shuttling through 14-3-3 and importin 7. (September 2016) - Mohammad, Dara K.; Nore, Beston F.; Gustafsson, Manuela O.; Mohamed, Abdalla J.; Smith, C.I. Edvard
Abstract: The Protein kinase B (AKT) regulates a plethora of intracellular signaling proteins to fine-tune signaling of multiple pathways. Here, we found that following B-cell receptor (BCR)-induced tyrosine phosphorylation of the cytoplasmic tyrosine kinase SYK and the adaptor BLNK, the AKT/PKB enzyme strongly induced BLNK (>100-fold) and SYK (>100-fold) serine/threonine phosphorylation (pS/pT). Increased phosphorylation promoted 14-3-3 binding to BLNK (37-fold) and SYK (2.5-fold) in a pS/pT-concentration dependent manner. We also demonstrated that the AKT inhibitor MK2206 reduced pS/pT of both BLNK (3-fold) and SYK (2.5-fold). Notably, the AKT phosphatase, PHLPP2 maintained the activating phosphorylation of BLNK at Y84 and increased protein stability (8.5-fold). In addition, 14-3-3 was required for the regulation SYK⿿s interaction with BLNK and attenuated SYK binding to Importin 7 (5-fold), thereby perturbing shuttling to the nucleus. Moreover, 14-3-3 proteins also sustained tyrosine phosphorylation of SYK and BLNK. Furthermore, substitution of S295 or S297 for alanine abrogated SYK⿿s binding to Importin 7. SYK with S295A or S297A replacements showed intense pY525/526 phosphorylation, and BLNK pY84 phosphorylation correlated with the SYK pY525/526 phosphorylation level. Conversely, the corresponding mutations to aspartic acid in SYK reduced pY525/526 phosphorylation. Collectively, these and previous results suggest that AKT and 14-3-3 proteins down-regulate the activity of several BCR-associated components, including BTK, BLNK and SYK and also inhibit SYK⿿s interaction with Importin 7.